Surface sizing agent and method for modifying PBO (poly (p-phenylenebenzobisoxazole)) fibers by using surface sizing agent
By uniformly adhering the coupling agent on the surface of the PBO fiber, the water-soluble polymethacrylate sizing agent grafted with modified nanoparticles, the problem of poor interfacial adhesion of PBO fibers is solved, significantly improving the fiber's pull-out strength and enhancing its application performance in composite materials.
Patent Information
- Application Number
- CN202510278830.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-05-02
AI Technical Summary
Due to the smooth surface and lack of polar functional groups, PBO fibers have poor interface adhesion with the resin matrix, which limits its application in the fields of elastic protection, aerospace structure, etc.
Water-soluble polymethacrylate is used as the sizing agent, and the coupling agent is doped in the sizing agent to graft modified nanoparticles, and they are uniformly attached to the surface of the PBO fiber by impregnation method to form a new anchor point to improve interface adhesion.
It significantly improves the interfacial adhesion of PBO fibers in composite materials, improves the synergistic effect between fibers and resins, enhances the fiber's pull-out strength, and meets the requirements of composite materials to interface adhesion.
Smart Images

Figure CN119912696A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of novel surface sizing agents and high-performance fiber materials, and discloses a surface sizing agent and a method for modifying PBO fibers by using the sizing agent. Background Art
[0002] PBO (poly(p-phenylene benzobisoxazole)) fiber is a polyaromatic liquid crystal high-performance fiber with the characteristics of high strength, high modulus, high temperature resistance and high flame retardancy. Its strength reaches 5.8 GPa, its modulus can reach 280 GPa, and its density is only 1.56 g / cm 3 , the limiting oxygen index is 68, the highest decomposition temperature can reach 650 ℃, and it has excellent chemical corrosion resistance and impact resistance. Its comprehensive performance is the best among organic fibers, and it is known as the super fiber of the 21st century. At present, PBO fiber has begun to be used in aerospace, human protection, armor protection and other composite materials. It is a high-end fiber material for both military and civilian use and has great application value.
[0003] However, due to the smooth surface and lack of polar functional groups, PBO fibers are extremely chemically inert and difficult to be impregnated with resins, resulting in poor interfacial adhesion with the resin matrix, poor synergy between the fiber and the resin, and difficulty in exerting the excellent mechanical properties of PBO fibers. The low interlaminar shear strength of PBO fiber composites greatly limits their application in the fields of anti-ballistic protection, aerospace structures, rubber reinforcement, and especially in the field of aerospace structural wave transmission.
[0004] Therefore, how to improve the interfacial adhesion between PBO fibers and composite materials through modification has become one of the urgent problems to be solved in this field. Summary of the invention
[0005] In order to solve the problems existing in the above-mentioned prior art, the present invention provides a surface sizing agent and a method for modifying PBO fiber using the sizing agent. Water-soluble polymethacrylate is used as the sizing agent, and coupling agent is doped into the sizing agent to graft modified nanoparticles. The water-soluble polymethacrylate sizing agent doped with coupling agent and graft modified nanoparticles is uniformly attached to the surface of the PBO fiber by an impregnation method. The obtained modified PBO fiber has good interface adhesion with the composite material. Compared with untreated PBO fiber and PBO fiber treated only with water-soluble polymethacrylate sizing, the modified PBO fiber obtained by the present invention based on impregnation sizing modification has better interface adhesion in the composite material. In addition, the above-mentioned modification method is simple to operate and has wide application and promotion value.
[0006] The specific concept of the present invention is as follows: On the basis of the commonly used water-soluble polymethacrylate sizing agent, the inventors obtained a new surface sizing agent by grafting nanoparticles onto the polymethacrylate sizing agent through a coupling agent grafting method. Compared with the method of coating the pure polymethacrylate sizing agent on the surface of PBO fibers, when the nanoparticles are added and coated on the surface of the PBO fibers, new anchoring points are formed between the PBO fibers and the composite material. When the fibers are pulled out of the composite material, the anchoring points are stressed, thereby synergistically improving the interfacial adhesion of the PBO fibers in the composite material, thereby improving the problem of poor interfacial adhesion of the PBO fibers in the composite material.
[0007] Based on the above inventive concept, the present invention first provides a surface sizing agent, specifically a silane coupling agent grafted modified nanoparticle / water-soluble polymethacrylate sizing agent, wherein the content of modified nanoparticles in the sizing agent is 0.2-3wt%, and the content of water-soluble polymethacrylate is 0.2-3wt%; wherein the nanoparticles are selected from nano-aramid fibers or nano-self-assembled tannic acid, both of which have active groups such as hydroxyl and carboxyl groups. The length of the above-mentioned nano-aramid fibers is controlled to be 10-100nm, or the particle diameter of the nano-self-assembled tannic acid is controlled to be 10-100nm.
[0008] The silane coupling agent is a coupling agent containing a methoxy group, mainly selected from KH570, KH792, etc., wherein the methoxy group contained therein can undergo a grafting reaction with the hydroxyl group of the nanoparticles.
[0009] The water-soluble polymethacrylate is selected from polymethyl methacrylate or polyethyl methacrylate, preferably polyethyl methacrylate, wherein the silane coupling agent and polyethyl methacrylate undergo a grafting reaction via a chemical bond.
[0010] After obtaining the above sizing agent, the inventors immersed the PBO fiber in the above silane coupling agent grafted modified nanoparticles / water-soluble polymethacrylate sizing agent, controlled the sizing amount to 0.1-2.8wt%, and obtained the modified PBO fiber after treatment.
[0011] Compared with the commonly used water-soluble polymethacrylate sizing agent, the modified PBO fiber adopts a coupling agent grafting method to graft nanoparticles into the polymethacrylate sizing agent. Compared with the method of coating the pure polymethacrylate sizing agent on the surface of the PBO fiber, when the nanoparticles are added and coated on the surface of the PBO fiber, a new anchor point is formed between the PBO fiber and the composite material. When the fiber is pulled out of the composite material, the anchor point is stressed, thereby synergistically improving the interfacial adhesion of the PBO fiber in the composite material. In addition, after the nanoparticles are treated by the coupling agent chemical grafting method, compared with the ordinary physical mixing and addition, they are more firmly attached to the surface of the PBO fiber by chemical bond connection, and are less likely to fall off over time.
[0012] The modified fibers were subjected to a single-filament pull-out test under epoxy resin conditions, and the pull-out strength of the modified fibers was increased to 52.5%, which can meet the requirements of composite materials for interface adhesion. In addition, the fiber elongation at break and tensile modulus are basically the same as before modification, indicating that the above modification has not affected the performance of the PBO fibers.
[0013] The inventors also provide a method for modifying PBO fiber using the above sizing agent, the specific steps are as follows: (1) Preparation of nanoparticles grafted with silane coupling agent Dissolve 1-15 g of nanoparticles in 500 ml of aqueous solution and disperse them ultrasonically for 30-80 min to prepare a nanoparticle dispersion. Then add 1-15 g of silane coupling agent and stir in a constant temperature shaker for 5-8 h. The temperature is set to 60-80 °C. The active groups of the nanoparticles, such as hydroxyl groups, react with the silane coupling agent to graft the nanoparticles onto the silane coupling agent.
[0014] (2) Preparation of silane coupling agent grafted modified nanoparticles / water-soluble polymethacrylate sizing agent 1-15 g of water-soluble polymethacrylate is added to the silane coupling agent grafted modified nanoparticle solution prepared in step (1), and the pH of the solution is adjusted to 6-7 with hydrochloric acid. The solution is stirred and dispersed for 30-80 min in a high-speed stirrer. The nanoparticles are grafted to the water-soluble polymethacrylate using the active groups of the coupling agent, and finally a silane coupling agent grafted modified nanoparticle / water-soluble polymethacrylate sizing agent is obtained.
[0015] (3) PBO fiber surface treatment The PBO fiber was immersed in an ethanol solution and ultrasonically treated at 30-40 °C for 2-3 h, during which the ethanol was replaced twice to remove impurities and oils on the fiber surface. Finally, it was washed twice with deionized water and placed in a vacuum oven at 60-100 °C for 4-6 h to completely remove moisture from the fiber surface.
[0016] (4) Preparation of modified PBO fibers with good bonding properties The PBO fiber treated in step (3) is immersed in the sizing agent of the silane coupling agent grafted modified nanoparticles / water-soluble polymethacrylate prepared in step (2), the sizing time is controlled to be 10-50 s, the temperature is controlled to be 30-50°C, and the sizing amount is controlled to be 0.1-2.8wt%, so that the silane coupling agent grafted modified nanoparticles / water-soluble polymethacrylate are uniformly attached to the surface of the PBO fiber. After the reaction is completed, the PBO fiber with the surface sizing modified is taken out, and repeatedly rinsed with deionized water, and vacuum dried at 50°C for 12 h to remove excess moisture from the fiber and the nanoparticles that are not firmly sized, thereby obtaining a modified PBO fiber with good bonding properties.
[0017] The above preparation method uses an impregnation method to coat the nanoparticles on the surface of the PBO fiber, forming a new anchor point at the interface between the PBO fiber and the composite material. When the composite material is subjected to an external force and the fiber is pulled out of the composite material, the anchor point bears more force, anchoring the fiber in the composite material, thereby synergistically improving the interfacial adhesion of the PBO fiber in the composite material. In addition, after the nanoparticles are treated by a coupling agent chemical grafting method, they are more firmly coated on the surface of the PBO fiber than ordinary physical mixing and adding chemical bonds, and are less likely to fall off as time increases. By regulating the concentration of nanoparticles and polymethacrylate and the reaction time, the sizing rate can be controlled to be adjustable within the above range to obtain PBO fibers with different interfacial bonding properties, which can meet the performance requirements of different usage scenarios.
[0018] The inventors also claim to protect the modified PBO fiber prepared by the above modification method.
[0019] In summary, the surface sizing agent and the method for modifying PBO fiber using the sizing agent provided by the present invention are universal, simple to operate, have low requirements on equipment conditions, are green and pollution-free, and the process is controllable. The sizing rate can be adjusted according to demand, and it is a very promising fiber surface modification method. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic diagram of the pull-out strength of the modified PBO fiber single filament prepared in Example 4. DETAILED DESCRIPTION
[0021] The present invention will be further described below in conjunction with specific embodiments, so that those skilled in the art can understand the present invention more comprehensively, but the present invention is not limited in any way. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0022] Example 1 A surface sizing agent and a method for modifying PBO fiber using the sizing agent, wherein the specific steps are as follows: (1) Preparation of nano-aramid fiber grafted with silane coupling agent KH570: 1 g of nano-aramid fiber with a length of 10-30 nm was dissolved in 500 ml of aqueous solution and ultrasonically dispersed for 50 min to prepare a nano-aramid fiber dispersion. Then, 1 g of silane coupling agent KH570 was added and stirred in a constant temperature shaker for 5 h at 60 °C. The active groups of the nano-aramid fiber, such as hydroxyl groups, reacted with the silane coupling agent KH570 to graft the nano-aramid fiber onto the silane coupling agent KH570. (2) Preparation of nano-aramid fiber grafted with silane coupling agent KH570 / water-soluble polyethyl methacrylate sizing agent: 1 g of water-soluble polyethyl methacrylate was added to the nano-aramid fiber solution grafted with silane coupling agent KH570 prepared in step (1), and the pH of the solution was adjusted to 7 with hydrochloric acid. The solution was stirred and dispersed in a high-speed stirrer for 60 min. The nano-aramid fiber was grafted onto the water-soluble polyethyl methacrylate using the active groups of the coupling agent KH570, and finally the nano-aramid fiber grafted with silane coupling agent KH570 / water-soluble polyethyl methacrylate sizing agent was obtained. (3) PBO fiber surface treatment: The PBO fiber was immersed in an ethanol solution and ultrasonically treated at 30 °C for 2 h, during which the ethanol was replaced twice to remove impurities and oil on the fiber surface. Finally, it was washed twice with deionized water and placed in a vacuum oven at 100 °C for 4 h to completely remove moisture from the fiber surface. (4) Preparation of modified PBO fiber with good bonding properties: Take an appropriate amount of the PBO fiber treated in step (3) and immerse it in the sizing agent prepared in step (2) by grafting modified nano-aramid fiber with silane coupling agent KH570 / water-soluble polyethyl methacrylate. The sizing time is controlled to be 30 s and the temperature is controlled to be 30 °C so that the grafted modified nano-aramid fiber with silane coupling agent KH570 / water-soluble polyethyl methacrylate is uniformly attached to the surface of the PBO fiber. After the reaction is completed, the surface-sizing modified PBO fiber is taken out and repeatedly rinsed with deionized water. It is vacuum dried at 50 °C for 12 h to remove excess moisture from the fiber and the unsizing solid nanoparticles to obtain a modified PBO fiber with good bonding properties.
[0023] It was detected that the sizing amount of the silane coupling agent KH570 grafted modified nano-aramid fiber / water-soluble polyethyl methacrylate sizing agent in the PBO fiber was 0.1wt%.
[0024] Further experimental tests show that the tensile strength of the unmodified PBO fiber is 5.6 GPa; the tensile strength of the modified PBO fiber is 5.6 GPa. Referring to GB / T 14288-2011 "Test method for interface shear strength of composite materials", a single-filament pull-out test was carried out under epoxy resin conditions. The single-filament pull-out strengths of the unmodified PBO fiber and the modified PBO fiber are 40 MPa and 46 MPa, respectively. After modification, the single-filament pull-out strength is increased by 15%.
[0025] Example 2 A surface sizing agent and a method for modifying PBO fiber using the sizing agent, wherein the specific steps are as follows: (1) Preparation of nano-aramid fiber grafted with silane coupling agent KH570: 2.5 g of nano-aramid fiber with a length of 10-30 nm was dissolved in 500 ml of aqueous solution and ultrasonically dispersed for 50 min to prepare a nano-aramid fiber dispersion. Then, 2.5 g of silane coupling agent KH570 was added and stirred in a constant temperature shaker for 5 h at 60 °C. The active groups of the nano-aramid fiber, such as hydroxyl groups, reacted with the silane coupling agent KH570 to graft the nano-aramid fiber onto the silane coupling agent KH570. (2) Preparation of nano-aramid fiber grafted with silane coupling agent KH570 / water-soluble polyethyl methacrylate sizing agent: 2.5 g of water-soluble polyethyl methacrylate was added to the nano-aramid fiber solution grafted with silane coupling agent KH570 prepared in step (1), and the pH of the solution was adjusted to 7 with hydrochloric acid. The solution was stirred and dispersed in a high-speed stirrer for 60 min. The nano-aramid fiber was grafted onto the water-soluble polyethyl methacrylate using the active groups of the coupling agent KH570, and finally the nano-aramid fiber grafted with silane coupling agent KH570 / water-soluble polyethyl methacrylate sizing agent was obtained. (3)-(4) Same as Example 1; It was detected that the sizing amount of the silane coupling agent KH570 grafted modified nano-aramid fiber / water-soluble polyethyl methacrylate sizing agent in the PBO fiber was 0.4wt%.
[0026] Further experimental tests showed that the tensile strength of the unmodified PBO fiber was 5.6 GPa, and the tensile strength of the modified PBO fiber was 5.5 GPa. In the single-filament pull-out test, the single-filament pull-out strengths of the unmodified PBO fiber and the modified PBO fiber were 40 MPa and 51 MPa, respectively, and the single-filament pull-out strength was increased by 27.5% after modification.
[0027] Example 3 A surface sizing agent and a method for modifying PBO fiber using the sizing agent, wherein the specific steps are as follows: (1) Preparation of nano-aramid fiber grafted with silane coupling agent KH570: 5 g of nano-aramid fiber with a length of 10-30 nm was dissolved in 500 ml of aqueous solution and ultrasonically dispersed for 50 min to prepare a nano-aramid fiber dispersion. Then, 5 g of silane coupling agent KH570 was added and stirred in a constant temperature shaker for 5 h at 60 °C. The active groups of the nano-aramid fiber, such as hydroxyl groups, reacted with the silane coupling agent KH570 to graft the nano-aramid fiber onto the silane coupling agent KH570. (2) Preparation of nano-aramid fiber grafted with silane coupling agent KH570 / water-soluble polyethyl methacrylate sizing agent: 5 g of water-soluble polyethyl methacrylate was added to the nano-aramid fiber solution grafted with silane coupling agent KH570 prepared in step (1), and the pH of the solution was adjusted to 7 with hydrochloric acid. The solution was stirred and dispersed in a high-speed stirrer for 60 min. The nano-aramid fiber was grafted onto the water-soluble polyethyl methacrylate using the active groups of the coupling agent KH570, and finally the nano-aramid fiber grafted with silane coupling agent KH570 / water-soluble polyethyl methacrylate sizing agent was obtained. (3)-(4) Same as Example 1; It was tested that the sizing amount of the silane coupling agent KH570 grafted modified nano-aramid fiber / water-soluble polyethyl methacrylate sizing agent in the PBO fiber was 0.8wt%.
[0028] Further experimental tests showed that the tensile strength of the unmodified PBO fiber was 5.6 GPa, and the tensile strength of the modified PBO fiber was 5.4 GPa. In the single-filament pull-out test, the single-filament pull-out strengths of the unmodified PBO fiber and the modified PBO fiber were 40 MPa and 55 MPa, respectively, and the single-filament pull-out strength was increased by 37.5% after modification.
[0029] Example 4 A surface sizing agent and a method for modifying PBO fiber using the sizing agent, wherein the specific steps are as follows: (1) Preparation of nano-aramid fiber grafted with silane coupling agent KH570: 10 g of nano-aramid fiber with a length of 10-30 nm was dissolved in 500 ml of aqueous solution and ultrasonically dispersed for 50 min to prepare a nano-aramid fiber dispersion. Then, 10 g of silane coupling agent KH570 was added and stirred in a constant temperature shaker for 5 h at 60 °C. The active groups of the nano-aramid fiber, such as hydroxyl groups, reacted with the silane coupling agent KH570 to graft the nano-aramid fiber onto the silane coupling agent KH570. (2) Preparation of nano-aramid fiber grafted with silane coupling agent KH570 / water-soluble polyethyl methacrylate sizing agent: 10 g of water-soluble polyethyl methacrylate was added to the nano-aramid fiber solution grafted with silane coupling agent KH570 prepared in step (1), and the pH of the solution was adjusted to 7 with hydrochloric acid. The solution was stirred and dispersed in a high-speed stirrer for 60 min. The nano-aramid fiber was grafted onto the water-soluble polyethyl methacrylate using the active groups of the coupling agent KH570, and finally the nano-aramid fiber grafted with silane coupling agent KH570 / water-soluble polyethyl methacrylate sizing agent was obtained. (3)-(4) Same as Example 1; It was tested that the sizing amount of the silane coupling agent KH570 grafted modified nano-aramid fiber / water-soluble polyethyl methacrylate sizing agent in the PBO fiber was 1.5wt%.
[0030] Further experimental tests show that the tensile strength of the unmodified PBO fiber is 5.6 GPa, and the tensile strength of the modified PBO fiber is 5.4 GPa. In the single-filament pull-out test, the single-filament pull-out strengths of the unmodified PBO fiber and the modified PBO fiber are 40 MPa and 61 MPa, respectively. After modification, the single-filament pull-out strength is increased by 52.5% (e.g. Figure 1 as shown).
[0031] Example 5 A surface sizing agent and a method for modifying PBO fiber using the sizing agent, wherein the specific steps are as follows: (1) Preparation of nano-aramid fiber grafted with silane coupling agent KH570: 15 g of nano-aramid fiber with a length of 10-30 nm was dissolved in 500 ml of aqueous solution and ultrasonically dispersed for 50 min to prepare a nano-aramid fiber dispersion. Then, 15 g of silane coupling agent KH570 was added and stirred in a constant temperature shaker for 5 h at 60 °C. The active groups of the nano-aramid fiber, such as hydroxyl groups, reacted with the silane coupling agent KH570 to graft the nano-aramid fiber onto the silane coupling agent KH570. (2) Preparation of nano-aramid fiber grafted with silane coupling agent KH570 / water-soluble polyethyl methacrylate sizing agent: 15 g of water-soluble polyethyl methacrylate was added to the nano-aramid fiber solution grafted with silane coupling agent KH570 prepared in step (1), and the pH of the solution was adjusted to 7 with hydrochloric acid. The solution was stirred and dispersed in a high-speed stirrer for 60 min. The nano-aramid fiber was grafted onto the water-soluble polyethyl methacrylate using the active groups of the coupling agent KH570, and finally the nano-aramid fiber grafted with silane coupling agent KH570 / water-soluble polyethyl methacrylate sizing agent was obtained. (3)-(4) Same as Example 1; It was tested that the sizing amount of the silane coupling agent KH570 grafted modified nano-aramid fiber / water-soluble polyethyl methacrylate sizing agent in the PBO fiber was 2.5wt%.
[0032] Further experimental tests showed that the tensile strength of the unmodified PBO fiber was 5.6 GPa, and the tensile strength of the modified PBO fiber was 5.2 GPa. In the single-filament pull-out test, the single-filament pull-out strengths of the unmodified PBO fiber and the modified PBO fiber were 40 MPa and 57 MPa, respectively, and the single-filament pull-out strength was increased by 42.5% after modification.
[0033] Compared with Examples 1-5, it can be seen that under the same experimental conditions, in Example 4, the content of nano-aramid fiber is 2wt%, the content of water-soluble polyethyl methacrylate is 2wt%, the sizing time is 30 s, and the sizing amount of silane coupling agent KH570 grafted modified nano-aramid fiber / water-soluble polyethyl methacrylate sizing agent in PBO fiber is finally controlled to be 1.5wt%, and the modified fiber has the most excellent interface bonding performance.
[0034] Example 6 A surface sizing agent and a method for modifying PBO fiber using the sizing agent, wherein the specific steps are as follows: (1) Preparation of nano-aramid fiber grafted with silane coupling agent KH792: 10 g of nano-aramid fiber with a length of 10-30 nm was dissolved in 500 ml of aqueous solution and ultrasonically dispersed for 50 min to prepare a nano-aramid fiber dispersion. Then, 10 g of silane coupling agent KH792 was added and stirred in a constant temperature shaker for 5 h at 60 °C. The active groups of the nano-aramid fiber, such as hydroxyl groups, reacted with the silane coupling agent KH792 to graft the nano-aramid fiber onto the silane coupling agent KH792. (2) Preparation of nano-aramid fiber grafted with silane coupling agent KH792 / water-soluble polyethyl methacrylate sizing agent: 10 g of water-soluble polyethyl methacrylate was added to the nano-aramid fiber solution grafted with silane coupling agent KH792 prepared in step (1), and the pH of the solution was adjusted to 7 with hydrochloric acid. The solution was stirred and dispersed in a high-speed stirrer for 60 min. The nano-aramid fiber was grafted onto the water-soluble polyethyl methacrylate using the active groups of the coupling agent KH792, and finally the nano-aramid fiber grafted with silane coupling agent KH792 / water-soluble polyethyl methacrylate sizing agent was obtained. (3) Same as Example 1; (4) Preparation of modified PBO fiber with good bonding properties: Take an appropriate amount of PBO fiber treated in step (3) and immerse it in the sizing agent prepared in step (2) by grafting modified nano-aramid fiber with silane coupling agent KH792 / water-soluble polyethyl methacrylate. The sizing time is controlled to be 30 s and the temperature is controlled to be 30 °C. The silane coupling agent KH792 grafted modified nano-aramid fiber / water-soluble polyethyl methacrylate is uniformly attached to the surface of the PBO fiber. After the reaction is completed, the surface-sized PBO fiber is taken out and repeatedly rinsed with deionized water. It is vacuum dried at 50 °C for 12 h to remove excess moisture from the fiber and the unsized nanoparticles to obtain a modified PBO fiber with good bonding properties.
[0035] It was tested that the sizing amount of the silane coupling agent KH792 grafted modified nano-aramid fiber / water-soluble polyethyl methacrylate sizing agent in the PBO fiber was 1.5wt%.
[0036] Further experimental tests showed that the tensile strength of the unmodified PBO fiber was 5.6 GPa, and the tensile strength of the modified PBO fiber was 5.4 GPa. In the single-filament pull-out test, the single-filament pull-out strengths of the unmodified PBO fiber and the modified PBO fiber were 40 MPa and 58 MPa, respectively, and the single-filament pull-out strength was increased by 45% after modification.
[0037] Example 7 A surface sizing agent and a method for modifying PBO fiber using the sizing agent, wherein the specific steps are as follows: (1) Preparation of nano self-assembled tannic acid modified by grafting with silane coupling agent KH570: 10 g of tannic acid was dissolved in 500 ml of aqueous solution, a certain amount of Tris buffer solution was added, the pH was adjusted to 8.5, and ultrasonic dispersion was performed for 50 min to prepare a nano self-assembled tannic acid dispersion. The particle diameter of the nano self-assembled tannic acid was 20-40 nm after detection. Then 10 g of silane coupling agent KH570 was added and stirred in a constant temperature shaker for 5 h. The temperature was set to 60 °C. The active groups of the nano self-assembled tannic acid, such as hydroxyl groups, reacted with the silane coupling agent KH570 to graft the nano self-assembled tannic acid particles onto the silane coupling agent KH570. (2) Preparation of silane coupling agent KH570 grafted modified nano self-assembled tannic acid / water-soluble polyethyl methacrylate sizing agent: 10 g of water-soluble polyethyl methacrylate was added to the silane coupling agent KH570 grafted modified nano self-assembled tannic acid solution prepared in step (1), and the pH of the solution was adjusted to 7 with hydrochloric acid. The solution was stirred and dispersed in a high-speed stirrer for 60 min. The nano self-assembled tannic acid was grafted onto the water-soluble polyethyl methacrylate using the active group of the coupling agent KH570, and finally the silane coupling agent KH570 grafted modified nano self-assembled tannic acid / water-soluble polyethyl methacrylate sizing agent was obtained. (3) Same as Example 1; (4) Preparation of modified PBO fiber with good bonding properties: Take an appropriate amount of PBO fiber treated in step (3) and immerse it in the sizing agent prepared in step (2) by grafting modified nano-self-assembled tannic acid / water-soluble polyethyl methacrylate with silane coupling agent KH570. The sizing time is controlled to be 30 s and the temperature is controlled to be 30 °C. The silane coupling agent KH570 grafted modified nano-self-assembled tannic acid / water-soluble polyethyl methacrylate is uniformly attached to the surface of the PBO fiber. After the reaction is completed, the PBO fiber with surface sizing modification is taken out and repeatedly rinsed with deionized water. It is vacuum dried at 50 °C for 12 h to remove excess moisture from the fiber and the unsizing nanoparticles to obtain a modified PBO fiber with good bonding properties.
[0038] It was tested that the sizing amount of the silane coupling agent KH570 grafted modified nano self-assembled tannic acid / water-soluble polyethyl methacrylate sizing agent in the PBO fiber was 1.5wt%.
[0039] Further experimental tests showed that the tensile strength of the unmodified PBO fiber was 5.6 GPa, and the tensile strength of the modified PBO fiber was 5.4 GPa. In the single-filament pull-out test, the single-filament pull-out strengths of the unmodified PBO fiber and the modified PBO fiber were 40 MPa and 56 MPa, respectively, and the single-filament pull-out strength was increased by 40% after modification.
[0040] Example 8 A surface sizing agent and a method for modifying PBO fiber using the sizing agent, wherein the specific steps are as follows: (1)-(3) are the same as in Example 4; (4) Preparation of modified PBO fiber with good bonding properties: Take an appropriate amount of PBO fiber treated in step (3) and immerse it in the sizing agent prepared in step (2) by grafting modified nano-aramid fiber with silane coupling agent KH570 / water-soluble polyethyl methacrylate. The sizing time is controlled to be 15 s and the temperature is controlled to be 30 °C. The silane coupling agent KH570 grafted modified nano-aramid fiber / water-soluble polyethyl methacrylate is uniformly attached to the surface of the PBO fiber. After the reaction is completed, the surface-sized PBO fiber is taken out and repeatedly rinsed with deionized water. It is vacuum dried at 50 °C for 12 h to remove excess moisture from the fiber and the unsized nanoparticles to obtain a modified PBO fiber with good bonding properties.
[0041] It was detected that the sizing amount of the silane coupling agent KH570 grafted modified nano-aramid fiber / water-soluble polyethyl methacrylate sizing agent in the PBO fiber was 1.0wt%.
[0042] Further experimental tests showed that the tensile strength of the unmodified PBO fiber was 5.6 GPa, and the tensile strength of the modified PBO fiber was 5.4 GPa. In the single-filament pull-out test, the single-filament pull-out strengths of the unmodified PBO fiber and the modified PBO fiber were 40 MPa and 53 MPa, respectively, and the single-filament pull-out strength was increased by 32.5%.
[0043] Example 9 A surface sizing agent and a method for modifying PBO fiber using the sizing agent, wherein the specific steps are as follows: (1)-(3) are the same as in Example 4; (4) Preparation of modified PBO fiber with good bonding properties: Take an appropriate amount of PBO fiber treated in step (3) and immerse it in the silane coupling agent KH570 grafted modified nano-aramid fiber / water-soluble polyethyl methacrylate sizing agent prepared in step (2). The sizing time is controlled to be 50 s and the temperature is controlled to be 30 °C. The silane coupling agent KH570 grafted modified nano-aramid fiber / water-soluble polyethyl methacrylate is uniformly attached to the surface of the PBO fiber. After the reaction is completed, the PBO fiber with surface sizing modification is taken out and repeatedly rinsed with deionized water. It is vacuum dried at 50 °C for 12 h to remove excess moisture from the fiber and the unsizing solid nanoparticles to obtain a modified PBO fiber with good bonding properties.
[0044] It was tested that the sizing amount of the silane coupling agent KH570 grafted modified nano-aramid fiber / water-soluble polyethyl methacrylate sizing agent in the PBO fiber was 1.8wt%.
[0045] Further experimental tests showed that the tensile strength of the unmodified PBO fiber was 5.6 GPa, and the tensile strength of the modified PBO fiber was 5.0 GPa. In the single-filament pull-out test, the single-filament pull-out strengths of the unmodified PBO fiber and the modified PBO fiber were 40 MPa and 58 MPa, respectively, and the single-filament pull-out strength was increased by 45%.
[0046] By comparing Examples 4, 8, and 9, it can be seen that under the same experimental conditions, in Example 4, the content of nano-aramid fiber is 2wt%, the content of water-soluble polyethyl methacrylate sizing agent is 2wt%, the sizing time is 30 s, and the sizing amount of silane coupling agent KH570 grafted modified nano-aramid fiber / water-soluble polyethyl methacrylate sizing agent in PBO fiber is finally controlled to be 1.5wt%, and the modified fiber has better interfacial bonding performance.
[0047] Comparative Example A PBO fiber modified by surface sizing, the specific preparation steps are as follows: (1) Preparation of water-soluble polyethyl methacrylate sizing agent: 10 g of water-soluble polyethyl methacrylate was added to 500 ml of aqueous solution, and ultrasonically dispersed for 50 min. The pH of the solution was adjusted to 7 with hydrochloric acid, and stirred and dispersed for 60 min under a high-speed stirrer to finally obtain a water-soluble polyethyl methacrylate sizing agent. (2) Surface treatment of PBO fibers: The PBO fibers were immersed in an ethanol solution and ultrasonically treated at 30 °C for 2 h, during which the ethanol was replaced twice to remove impurities and oils on the fiber surface. Finally, the fibers were washed twice with deionized water and placed in a vacuum oven at 100 °C for 4 h to completely remove moisture from the fiber surface. (3) Preparation of modified PBO fiber: Take an appropriate amount of PBO fiber treated in step (2) and immerse it in the water-soluble polyethyl methacrylate sizing agent prepared in step (1). The sizing time is controlled to be 30 s and the temperature is controlled to be 30 °C. The water-soluble polyethyl methacrylate is uniformly attached to the surface of the PBO fiber. After the reaction is completed, the surface-sized PBO fiber is taken out and repeatedly rinsed with deionized water. It is vacuum dried at 50 °C for 12 h to remove excess moisture from the fiber and unsized and firmly bonded nanoparticles, thereby obtaining a modified PBO fiber with good bonding properties.
[0048] The results show that the sizing amount of water-soluble polyethyl methacrylate sizing agent in PBO fiber is 1.5wt%.
[0049] Further experimental tests showed that the tensile strength of the unmodified PBO fiber was 5.6 GPa, and the tensile strength of the modified PBO fiber was 5.4 GPa. In the single-filament pull-out test, the single-filament pull-out strengths of the unmodified PBO fiber and the modified PBO fiber were 40 MPa and 45 MPa, respectively, and the single-filament pull-out strength was increased by 12.5%.
[0050] Compared with the control example, it can be seen that under the same experimental conditions, in Example 4, when the content of the grafted modified nano-aramid fiber with the coupling agent KH570 is 2wt%, the single fiber pull-out strength is higher and the modified fiber has more excellent interface bonding performance.
[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any equivalent substitutions, modifications, etc. made by technicians in this field without any creative work within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A surface sizing agent, characterized in that: Specifically, it is a silane coupling agent grafted modified nanoparticle / water-soluble polymethacrylate sizing agent, wherein the content of nanoparticles in the sizing agent is 0.2-3wt%, and the content of water-soluble polymethacrylate is 0.2-3wt%; wherein the nanoparticles are selected from nano-aramid fibers or nano-self-assembled tannic acid; wherein the length of the nano-aramid fibers is 10-100nm, and the particle diameter of the nano-self-assembled tannic acid is 10-100nm.
2. The surface sizing agent according to claim 1, characterized in that: The silane coupling agent is a coupling agent containing a methoxy group, and the water-soluble polymethacrylate is polymethyl methacrylate or polyethyl methacrylate.
3. The surface sizing agent according to claim 1 or 2, characterized in that: The silane coupling agent is selected from KH570 or KH792, and the water-soluble polymethacrylate is selected from polyethyl methacrylate.
4. A method for modifying PBO fiber using the surface sizing agent of claim 1, characterized in that: The specific steps are as follows: (1) Preparation of nanoparticles grafted with silane coupling agent; (2) Preparation of silane coupling agent grafted modified nanoparticles / water-soluble polymethacrylate sizing agent; (3) PBO fiber surface treatment; (4) Preparation of modified PBO fibers with good bonding properties; The content of nanoparticles in the sizing agent in step (2) is 0.2-3wt%, the content of water-soluble polymethacrylate is 0.2-3wt%, and the nanoparticles are selected from nano-aramid fibers or nano-self-assembled tannic acid; wherein the length of the nano-aramid fibers is 10-100nm, and the particle diameter of the nano-self-assembled tannic acid is 10-100nm.
5. The method for modifying PBO fiber according to claim 4, characterized in that: Step (1) Preparation of nanoparticles grafted with silane coupling agent, the specific steps are as follows: Dissolve 1-15 g of nanoparticles in 500 ml of aqueous solution and disperse them ultrasonically for 30-80 min to prepare a nanoparticle dispersion. Then add 1-15 g of silane coupling agent and stir in a constant temperature shaker for 5-8 h at 60-80 °C to graft the nanoparticles onto the silane coupling agent.
6. The method for modifying PBO fiber according to claim 4, characterized in that: Step (2) Preparation of silane coupling agent grafted modified nanoparticles / water-soluble polymethacrylate sizing agent, the specific steps are as follows: 1-15 g of water-soluble polymethacrylate is added to the silane coupling agent grafted modified nanoparticle solution prepared in step (1), and the pH of the solution is adjusted to 6-7 with hydrochloric acid. The solution is stirred and dispersed for 30-80 min under a high-speed stirrer to graft the nanoparticles onto the water-soluble polymethacrylate, thereby finally obtaining silane coupling agent grafted modified nanoparticles / water-soluble polymethacrylate sizing agent.
7. The method for modifying PBO fiber according to claim 4, characterized in that: Step (3) PBO fiber surface treatment, the specific steps are as follows: The PBO fiber was immersed in an ethanol solution and ultrasonically treated at 30-40 °C for 2-3 h, during which the ethanol was replaced twice to remove impurities and oils on the fiber surface. Finally, it was washed twice with deionized water and placed in a vacuum oven at 60-100 °C for 4-6 h to completely remove moisture from the fiber surface.
8. The method for modifying PBO fiber according to claim 4, characterized in that: Step (4) Preparation of modified PBO fiber with good bonding properties, the specific steps are as follows: The PBO fiber treated in step (3) is immersed in the sizing agent of the silane coupling agent grafted modified nanoparticles / water-soluble polymethacrylate prepared in step (2), the sizing time is controlled to be 10-50 s, the temperature is controlled to be 30-50°C, and the sizing amount is controlled to be 0.1-2.8wt%, so that the silane coupling agent grafted modified nanoparticles / water-soluble polymethacrylate are uniformly attached to the surface of the PBO fiber. After the reaction is completed, the PBO fiber with the surface sizing modified is taken out, and repeatedly rinsed with deionized water, and vacuum dried at 50°C for 12 h to remove excess moisture from the fiber and the nanoparticles that are not firmly sized, thereby obtaining a modified PBO fiber with good bonding properties.
Citation Information
Patent Citations
Sizing agent-coated reinforcing fibers, method for producing sizing agent-coated reinforcing fibers, prepreg, and fiber-reinforced composite material
CN106068346A
PBO fiber sizing agent containing benzoxazole diamine compatilizer and application of PBO fiber sizing agent
CN112760972A
Sizing agent for surface modification of PBO (poly (p-phenylene benzobisoxazole)) fibers as well as preparation method and application of sizing agent
CN118186773A